2023
DOI: 10.1186/s12889-022-14926-8
|View full text |Cite
|
Sign up to set email alerts
|

Low influenza vaccine uptake by healthcare workers caring for the elderly in South African old age homes and primary healthcare facilities

Abstract: Background The elderly bear the highest burden of South Africa’s estimated annual > 10 million influenza cases and > 11,000 influenza-related deaths. Unvaccinated healthcare workers (HCWs) are at high occupational risk of contracting influenza, and may transmit influenza to elderly patients in their care. Thus, the South African National Department of Health recommends that HCWs receive annual influenza vaccination. This study aimed to determine influenza vaccination coverage among HCWs; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
(96 reference statements)
0
3
1
Order By: Relevance
“…Although these comparisons are limited due to differences in study sites and the HCW definition, which was expanded to include all types of HCW working in the hospital in this study as opposed to only doctors or medical service providers in the past studies [22,23], they indicate that HCW in Nakhon Phanom may be more hesitant towards influenza vaccines than normally expected. Our result is also slightly higher compared to studies in countries such as Egypt, Hong Kong, and South Africa, where influenza vaccine hesitancy among HCWs was reported to be below 50% [33][34][35][36].…”
Section: Discussioncontrasting
confidence: 80%
“…Although these comparisons are limited due to differences in study sites and the HCW definition, which was expanded to include all types of HCW working in the hospital in this study as opposed to only doctors or medical service providers in the past studies [22,23], they indicate that HCW in Nakhon Phanom may be more hesitant towards influenza vaccines than normally expected. Our result is also slightly higher compared to studies in countries such as Egypt, Hong Kong, and South Africa, where influenza vaccine hesitancy among HCWs was reported to be below 50% [33][34][35][36].…”
Section: Discussioncontrasting
confidence: 80%
“…Among healthcare professionals, the vaccination coverage varied from 20 to 56% in the LMICs under study [ 10 ]. The potential cause for the low vaccination coverage may be attributed to the suboptimal rates of influenza vaccine uptake [ 11 14 ]. Research conducted on populations at high risk for influenza revealed varying rates of influenza vaccine uptake [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The potential cause for the low vaccination coverage may be attributed to the suboptimal rates of influenza vaccine uptake [ 11 14 ]. Research conducted on populations at high risk for influenza revealed varying rates of influenza vaccine uptake [ 11 14 ]. Specifically, the uptake of the influenza vaccine was observed to be 33.3% among healthcare workers, 5.4% among elderly individuals, 27% among pregnant women, and 33.7% among adults with co-morbid conditions [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, vaccination is an effective tool in preventing influenza and serious cases and hospitalizations related to this disease 4 . Health workers are one of the priority groups for which the influenza vaccine is recommended annually 5 . However, studies conducted in different places in the world often show low coverage of influenza vaccine among health workers, which can have repercussions on illness, absenteeism, and transmission of influenza to patients, compromising the adequate functioning of health services 6,7 .…”
Section: Introductionmentioning
confidence: 99%